The Roles of The Persian People To The Glory of The Abbasiyah Dynasty In The Time Of Caliph Harun Al-Rashid (786-809 AD) - Rusydi, Ibnu; Didin Saepudin; Murodi (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2023)
This paper aims to study and analyze how far the roles of the Persians to the glory of the Abbasid dynasty during the Caliph Harun al-Rashid (786-809 AD). The research method is a historical method which is a process of critically examining and analyzing past records and relics. This study concludes that the reign of Caliph Harun al-Rashid was a period of Persian domination. This is because first The policy of the Abbasid dynasty in the early days was to provide great opportunities and opportunities for the Mawali of Persian descent in various fields of government. Second, the strong Persian influence is marked by the move of the capital to Baghdad, which is located in an area that is heavily influenced by Persian culture. Third, the position of prime minister (wazir) was entrusted to a family of Persian descent, namely the Barmak family. The ministers of Persian descent were given full powers to carry out their duties in the government. Fourth, the Baitul Hikmah Library which is a center for research, development, and transfer of knowledge is led by a Persian and employs many Persians.